DITERPENE ALKALOID FROM DELPHINIUM OREOPHILUM AND ANTIOXIDANT ACTIVITY (Scientific journal of the Fergana State University, 2024)
The aerial parts of the Delphinium oreophilum plant was harvested from the mountain slopes of Zomin and Yangikurgan districts. In order to study the alkaloids contained in the plant, the plant was dried in a cool place, crushed and extracted with 70% ethyl alcohol. The alcoholic extract of the plant was divided into ethyl acetate and chloroform fractions. A sum of diterpene alkaloids was isolated from the chloroform fraction. The obtained compounds were analyzed by 1H and 13C NMR spectra. Antioxidant activity was performed by DPPH assay. The results of the analysis were analyzed and one of the compounds was found to be Lycoctonine. The antioxidant activity of the compound in different concentrations was studied.